Practical experience with the implementation of an athlete's biological profile in athletics, cycling, football and swimming. Issue 10 (19th March 2014) - Zorzoli, M; Pipe, A; Garnier, P Y; Vouillamoz, M; Dvorak, J
Abstract : The introduction of the athlete's biological passport (ABP) has been a milestone in the fight against doping. The ABP is a collection of measurements of different biological parameters influenced by the administration of doping agents through the time and for each athlete. Two different modules have been developed and validated so far: the haematological module, which aims to identify enhancement of oxygen transport, including use of erythropoiesis-stimulating agents and any form of blood transfusion or manipulation, which became effective in 2010; and the steroidal module, which intends to detect the use of endogenous anabolic androgenic steroids when administered exogenously and other anabolic agents, which was introduced in 2014. Prior to the implementation of the haematological module, it is important to define an athlete's testing pool on whom to collect blood and/or urine in-competition and out-of-competition (for the steroidal module, this is irrelevant because all collected urine samples will be subjected to analysis for the steroidal variables) and to be compliant with the strict requirements of the World Anti-Doping Agency ABP Operating Guidelines. The established individual profile can be used either to target traditional antidoping tests (recombinant erythropoietins, or homologous blood transfusion tests for the haematological module; isotope ratio mass spectrometry (IRMS) for the steroidal module) or to support an antidoping rule violation due to the use of a forbidden substance or method. In this article, we present the experience of four major International Federations which have implemented an ABP programme, focusing on the haematological module. They constitute examples which could be followed by other antidoping organisations wishing to introduce this new, efficient and innovative antidoping tool.